Expression analysis of drug-resistant gene (blaOXA-51) in carbapenemases producing Acinetobacter baumannii treated with imipenem/sulbactam combination - Saber Noshadi; Alireza Khodavandi (Universidade de São Paulo, 2021)
Drug-resistant Acinetobacter baumannii is a frightening reality. The aim of this study is to examine the expression profiles of blaOXA-51 gene in carbapenemases producing A. baumannii treated with imipenem/sulbactam combination. Carbapenemases producing A. baumannii was identified among clinical isolates of A. baumannii obtained from patients at Shahid Rajaee hospital, Gachsaran, Iran, from January to June 2018. Synergism testing of imipenem/sulbactam on carbapenemases producing A. baumannii was carried out by broth microdilution method. Eventually, the expression of blaOXA-51 gene was carried out to investigate the inhibitory properties of imipenem/sulbactam combination against carbapenemases producing A. baumannii using quantitative real time RT-PCR. Among A. baumannii isolates, 24% were carbapenemases producing A. baumannii. Imipenem/sulbactam combination revealed synergistic and partial synergistic effect for all tested isolates (FIC= 0.313-0.75). Finally, imipenem/sulbactam combination displayed significant down-regulation of blaOXA-51 gene in carbapenemases producing A. baumannii. Imipenem synergizes with sulbactam against carbapenemases producing A. baumannii by targeting of the blaOXA-51 gene.